PENERAPAN TERAPI RELAKSASI AUTOGENIK PADA PASIEN POST ULKUS DIABETIKUM DALAM MENGATASI KETIDAKSTABILAN KADAR GLUKOSA DARAH DI RSUD Prof.M.YAMIN.SH PARIAMAN - ALPICES; MECHI SILVIA DORA; ZELVIA PRAMESTI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2026)
Diabetic foot ulcers are chronic wounds that are difficult to heal. Tissue damage in diabetic foot ulcers is caused by neurological (neuropathy) and vascular disorders in the legs. These disorders do not directly cause diabetic foot ulcers, but rather begin with a mechanism that reduces pain sensation, causes callus formation, and reduces blood flow that carries oxygen and nutrients to the tissues. One treatment option for managing diabetic ulcers to maintain stable blood glucose levels is non-pharmacological therapy in the form of autogenic relaxation. Autogenic relaxation is a technique for relaxing the body and mind. This study used a case study method with a nursing care approach. The assessment was conducted on patients with diabetic ulcers. The nursing intervention was autogenic relaxation therapy. The results of the intervention were evaluated by measuring glucose levels before and after the relaxation. The results of the application showed that autogenic relaxation performed for 3 consecutive days can reduce random glucose levels in patients with diabetic ulcers and unstable blood glucose levels, with an average decrease of 10-15 mg/dL. It can be concluded that the application of autogenic relaxation can reduce random blood glucose levels in patients with Type 2 DM. Keywords: Diabetic ulcers, unstable blood glucose levels, autogenic relaxation